Malaysian Social Issues and their Categories: A Meta- Analysis - Saleh, Sofiazianti; Mohamad Ashari, Zakiah; Mohd Kosnin, Azlina; Farhana Zainudin , Nurul (International Journal of Psychosocial Rehabilitation, 2020)
The concept of a ‘social issue’ can be thought of in many ways, with the definition differing depending on the thinker’s perspective. This often leads to a degree of confusion and misalignment on what exactly constitutes a ‘social issue.’ Most broadly, a ‘social issue’ can be thought of as a problem that influences or affects a considerable number of people within a society. These must be distinguished from the standard ‘personal life’ issues faced by all members of society and from the economic issues every nation faces. The identification of prevalent social issues within Malaysia requires a clear vision as to which segments of society require the most and most immediate attention. Thus, this study aims to identify categories to understand what constitutes a social issue and to clarify what the term means in a Malaysian context based on previous studies via meta-analysis techniques. There were 30 journal articles collected from SAGE Journal and ScienceDirect starting from 2010 to date . After a review analysis, there are seven categories of social issues: (1) falling prey to abuse ; (2) committing crime; (3) obstacles to employment; (4) quality of living condition; (5) obstacles to healthcare; (6) obstacles to education; and (7) engaging in vice.